Cognitive performance of youth with primary generalized anxiety disorder versus primary obsessive–compulsive disorder. Issue 2 (29th October 2018) - Kim, Kerri L.; Christensen, Rachel E.; Ruggieri, Amanda; Schettini, Elana; Freeman, Jennifer B.; Garcia, Abbe M.; Flessner, Christopher; Stewart, Elyse; Conelea, Christine; Dickstein, Daniel P.
Abstract : Background: Despite gains made in the study of childhood anxiety, differential diagnosis remains challenging because of indistinct boundaries between disorders and high comorbidity. This is certainly true for generalized anxiety disorder (GAD) and obsessive–compulsive disorder (OCD) as they share multiple cognitive processes (e.g., rumination, intolerance of uncertainty, and increased attention to threat). Disentangling such cognitive characteristics and, subsequently, underlying mechanisms could serve to inform assessment and treatment practices, and improve prognoses. Methods: The current study sought to compare the cognitive performance (working memory, visuospatial memory, planning ability/efficiency, and cognitive flexibility), indexed by the Cambridge Neuropsychological Automated Battery (CANTAB) among three nonoverlapping groups of youth: (1) those diagnosed with OCD ( n = 28), (2) those diagnosed with GAD, not OCD ( n = 34), and (3) typically‐developing controls (TDC) ( n = 65). Results: Results showed that OCD and GAD youth demonstrated neurocognitive deficits in planning ability/efficiency, cognitive flexibility, and visual processing when compared to TDC, with potential diagnostic specificity such that youth with GAD or OCD had unique deficits compared to TDC and to one another. Specifically, youth with OCD demonstrated significantly impaired planning ability compared to youth in the GAD and TDS groups, whereas youth with GAD demonstrated greater cognitive inflexibility and delayed visual processing compared to youth in the OCD and TDC groups. Conclusions: Future studies should expand upon these findings with more comprehensive assessment of cognitive functioning by including self‐ and parent‐report forms, and neuroimaging to link behavioral findings with subjective ratings and neurocircuitry. Altogether, data can then inform future assessment and treatment targets.